Effects of a pre-fabricated corrector appliance in the early treatment of anterior crossbite in Class III malocclusion - Huilca, Gonzalo Paúl Velásquez (2021)
Introduction: In Class III malocclusion, interception in the deciduous and mixed dentitions is of clinical interest, because of the limited possibilities of intervention. Recently, a pre-fabricated appliance has been developed to correct Class III malocclusions in the deciduous and mixed dentitions. However, the effects of this device have not been studied and described in the literature. Objective: The aim of the present prospective study was to cephalometrically evaluate the effects and to assess the effectiveness and clinical performance of the Ortho-Tain Class III Corrector Appliance in the early correction of anterior crossbite in Class III malocclusion. Methods: The sample consisted of 2 groups. The experimental group comprised 22 patients treated with the Ortho-Tain Class III Corrector Appliance, during a mean period of 20. The control group comprised 22 untreated subjects with Class III malocclusion with or without anterior crossbite who presented lateral cephalograms. Intergroup comparison of treatment and normal growth changes were compared with t and Mann-Whitney tests. Results: There was a significant difference in the mandibular plane angle changes because it decreased in the treated patients and increased in the control group. Additionally, the lower anterior face height increase and maxillary molar vertical development were significantly smaller in the treatment group. There was a significant decrease in the number of patients with anterior crossbite and edge-to-edge relationships, during treatment, in the experimental group. Conclusions: This appliance produced counter-clockwise rotation of the mandibular plane, smaller lower anterior face height increase and maxillary molar vertical development, improvement of anterior crossbite in 75% of the patients and therefore, it is an important alternative for early Class III malocclusion treatment.